Tracking Land Use Land Cover changes from 2000 to 2018 in a local area of East Java Province, Indonesia - Indarto Indarto; Hakim Farid Lukman (Bulletin of Geography. Socio-Economic Series, 2021)
Land Use Land Cover (LULC) changes represent human influences on the natural ecosystem. This study aims to analyse such changes in the eastern part of East Java, a region of ± 3320.3 km2. The changes are analysed by comparing two editions of maps (the National Digital Map and Landsat-8). Five subsets are explored to understand the LULC changes caused by the development of: transportation infrastructure; industrial sites; the agricultural sector; tourism; urbanisation; and sub-urbanisation. Regional development from 2000 to 2018 has increased built-up areas by 40.55% (122.5 km2), while paddy fields have increased by 71.08%, and forest plantation areas by 16.03%. Conversely, the development has reduced rural areas by 61.06% (860.1 km2) and water bodies by 54.02% (44.52 km2). The LULC has significantly changed the natural landscape to a human-dominated landscape, which is potentially fragile in the face of the disasters to which the region is prone.